Colonoids From Patients With Pediatric Inflammatory Bowel Disease Exhibit Decreased Growth Associated With Inflammation Severity and Durable Upregulation of Antigen Presentation Genes. Issue 2 (19th June 2020) - Kelsen, Judith R; Dawany, Noor; Conrad, Maire A; Karakasheva, Tatiana A; Maurer, Kelly; Wei, Jane M; Uman, Selen; Dent, Maiah H; Behera, Rithika; Bryant, Laura M; Ma, Xianghui; Moreira, Leticia; et al.
Abstract: Background: Defining epithelial cell contributions to inflammatory bowel disease (IBD) is essential for the development of much needed therapies for barrier repair. Children with very early onset (VEO)-IBD have more extensive, severe, and refractory disease than older children and adults with IBD and, in some cases, have defective barrier function. We therefore evaluated functional and transcriptomic differences between pediatric IBD (VEO and older onset) and non-IBD epithelium using 3-dimensional, biopsy-derived organoids. Methods: We measured growth efficiency relative to histopathological and clinical parameters in patient enteroid (ileum) and colonoid (colon) lines. We performed RNA-sequencing on patient colonoids and subsequent flow cytometry after multiple passages to evaluate changes that persisted in culture. Results: Enteroids and colonoids from pediatric patients with IBD exhibited decreased growth associated with histological inflammation compared with non-IBD controls. We observed increased LY Z expression in colonoids from pediatric IBD patients, which has been reported previously in adult patients with IBD. We also observed upregulation of antigen presentation genes HLA-DRB1 and HLA-DRA, which persisted after prolonged passaging in patients with pediatric IBD. Conclusions: We present the first functional evaluation of enteroids and colonoids from patients with VEO-IBD and older onset pediatric IBD, a subset of which exhibits poor growth. Enhanced, persistent epithelial antigen presentation gene expression in patient colonoids supports the notion that epithelial cell-intrinsic differences may contribute to IBD pathogenesis. Graphical Abstract: